A bottom-up approach to design wearable and stretchable smart fibers with organic vapor sensing behaviors and energy storage properties. Issue 28 (28th June 2018) - Marriam, Ifra; Wang, Xingping; Tebyetekerwa, Mike; Chen, Guoyin; Zabihi, Fatemeh; Pionteck, Jürgen; Peng, Shengjie; Ramakrishna, Seeram; Yang, Shengyuan; Zhu, Meifang
Abstract : Wetspinning and electrospinning were employed in a bottom-up approach to fabricate fibers for organic vapor sensors and energy storage. Abstract : Realizing the best way to integrate electronics and textiles to develop smart wearable, functional apparel with multiple functionalities such as fibers with a unified capability to store and utilize energy is a significant topic of concern recently. Therefore, presenting a facile approach to obtain fibers with such unique properties in a continuous process is a forward contributing step towards the development of this field. Herein, a bottom-up approach to fabricate stretchable poly(styrene-butadiene-styrene)/few-layer graphene composite (SBS-G) fibers with unique organic vapor sensing behaviors and modified SBS-G fibers coated with electroactive carbon black (CB) nanofibers via modified electrospinning with excellent energy storage properties is presented. Unlike conventional conductive polymer composites (CPCs) that respond only to polar or non/low-polar organic vapors, the fabricated SBS-G composite fibers exhibited high sensitivity, excellent reversibility, and reproducibility as well as fast response to both polar and non/low-polar organic vapors. Moreover, the modified nanofiber-based SBS-G fibers demonstrated a high capacitive performance (78 F cm −3 ), energy and power density (6.6 mW h cm 3 and 692 mW cm 3 ) and excellent flexibility. This study provides guidelines for the fabrication of ideal organic vapor sensors based on polymer composite fibers and an approach to modify any "off-the-shelf fiber" for fiber-based power storage.